Significance of cardiovascular evaluation in patients with moderate Chronic Obstructive Pulmonary Disease (COPD) - Buklioska Ilievska, Daniela; Minov, Jordan (Publi Créations, 2020)
Introduction Chronic obstructive pulmonary disease (COPD) with prevalence 5-13% is a major cause of morbidity and mortality in the world and fourth leading cause after myocardial infarction, malignant diseases and cerebrovascular incidents. The main cause of morbidity and mortality in COPD patients are cardiovascular diseases. COPD is an independent cardiovascular risk factor even in mild and moderate stage of the disease, due to persistent low-grade systemic inflammation. Early diagnosis and treatment of cardiovascular morbidity in COPD patients is important for improving life quality and prognosis. Aim To evaluate cardiovascular morbidity in patients with moderate COPD. Material and methods Cross-sectional study. Investigated group: 63 patients (40 male, 23 female) with diagnosed moderate COPD (forced expiratory volume in 1st second - FEV1 50-80%) according to GOLD (Global Initiative for Chronic Obstructive Lung Disease) criteria and according to ABCD classification: 60% (B), 40%(A). Control group - 30 subjects with normal spirometry (without COPD) as controls. Inclusion criteria for both groups: age 40-75, cigarette smoking history >=10 pack/years, signed consent for participation and clinically stable condition at least 6 weeks prior enrolment. Exclusion criteria: other chronic or acute pulmonary disease, diabetes mellitus, valvular heart disease, left ventricular hypertrophy, body mass index>35 kg/m^2, liver or renal failure, anaemia, muscle disorders, patients who do not want to participate. All patients underwent pulmonary function tests (spirometry and gas analysis), chest-X ray in two directions (postero-anterior and latero-lateral position), resting electrocardiogram (ECG), 24 hour-ECG-Holter monitoring, two-dimensional (2D)Doppler echocardiography, Doppler-ultrasound of lower limb and carotid arteries. Results The COPD group showed significantly higher prevalence of right ventricular (RV) abnormalities. RV systolic dysfunction was present in 47,61%, pulmonary hypertension (PH) in 23,8%, tricuspid regurgitation as most frequent valvular abnormality in 14,28%, left ventricular (LV) systolic dysfunction in 14,28%. Electrocardiography results obtained premature ventricular (PVCs) contractions in 6,34%, p-pulmonale in 7,93%, right bundle branch block (RBBB) in 4,76%. There was significant difference between normal ECG findings in patients with moderate COPD 8,33% versus 76,67% in control group. 24-hour-ECG-Holter monitoring allowed detection of arrhythmias in asymptomatic patients, and detected abnormalities were significantly higher compared to resting ECG. 24h-ECG-Holter monitoring revealed premature supraventricular (PSCs) contractions in 38,1%, sinus tachycardia in 33,3%, PVCs in 47,6%, PVCs pairs in 14,3%, PVCs couplets in 9,5%, un-sustained ventricular tachycardia in 4,8%. Carotid plaques without stenosis were detected in 33,3%, with stenosis less than 40% of the arterial lumen in 9,5%, with stenosis 40-60% of the lumen in 4,76% and intima-media thickness (IMT) > 0,5mm in 28,6%. According to this, in the control group 10 patients (33,33%) had normal finding, 12 (40%) had thickened IMT and 8 patients (26,67%) non-stenotic atherosclerotic plaques. Frequency of peripheral artery disease in COPD patients based on Doppler ultrasonography of lower limb arteries was significantly higher in COPD 61,93% versus 43.33% in the control group. 7 Conclusion Cardiovascular evaluation in patients with moderate COPD is very important because of the increased risk of cardiovascular incidents in the early stage of the disease. Integrated-care approach for COPD patients is significant for early detection of unrecognized coexisting cardiac disorders.
Keywords: COPD; echocardiography; pulmonary hypertension; arrhythmias; electrocardiogram